The impact of clozapine on hospital use: a systematic review and meta‐analysis. (3rd February 2017) - Land, R.; Siskind, D.; McArdle, P.; Kisely, S.; Winckel, K.; Hollingworth, S. A.
Abstract : Objective: The objective of this study was to perform a systematic review and meta‐analysis of studies reporting the impact of clozapine on hospital use in people with a psychotic illness. Method: PubMed, EMBASE, PsycINFO and the Cochrane Schizophrenia Group Trials Register were systematically searched from inception to 12 October 2016. We included all trials and observational studies, except case reports. Results: Thirty‐seven studies were included. Clozapine significantly reduced the proportion of people hospitalised compared to control medicines (RR = 0.74; 95% CI: 0.69–0.80, P < 0.001, 22 studies, n = 44 718). There were significantly fewer bed days after clozapine treatment compared to before clozapine treatment in both controlled (MD = −34.41 days; 95% CI: −68.22 to −0.60 days, P = 0.046, n = 162) and uncontrolled studies (MD = −52.86 days; 95% CI: −79.86 days to −25.86 days, P < 0.001, n = 2917). Clozapine and control medicines had a similar time to rehospitalisation (−19.90 days; 95% CI: −62.42 to 22.63 days, P = 0.36). Conclusion: Clozapine treatment reduced the number of people hospitalised and the number of bed days after treatment compared with before treatment. Clozapine has the potential to reduce acute hospital use among people with treatment refractory schizophrenia.